Estudo técnico e ambiental de barragem de terra na zona rural de Água Nova/RN - Barbosa, Sávio Felipe Pereira (Universidade Federal Rural do Semi-Árido, 2018)
Dam is the term that is associated with all engineering work that has as purpose the of a water course for retention of its volume. Among the purposes are supply, electricity generation, navigation, etc. The dams are classified according to construction materials and methods, they can be of land or concrete, typologies more common in the civil environment. The design of a should take into account a set of factors, such as characteristics of watercourses, regional topography, the presence of deposits near the site, among other factors that verified the technical and economic viability of the construction. Based on this thought, this work had as main objective to study the physical characteristics of a dam of earth located in the site Nafuê, belonging to the municipality of Água Nova, Rio Grande do Norte. In addition to a bibliographical review, the work has an important technical collection regarding the characterization of the soil used in the work, data obtained from tests of granulometry, compaction, specific mass, plasticity limit, among others. The research revealed that the work does not have the minimum characteristics referenced and that during the enlargement process, the necessary studies for a work of this size, related to construction technique and materials, as well as to environmental issues, important point of debate in the days current.
Keywords: Barragem; Geotecnia; Solo; Meio ambiente; ENGENHARIAS::ENGENHARIA CIVIL